A Life Worth Living: Evidence on the Relationship Between Prosocial Values and Happiness. (May 2015) - Moynihan, Donald P.; DeLeire, Thomas; Enami, Kohei
Employees with a desire to help others provide benefits to their organization, clients, and fellow workers, but what do they get in return? We argue that the prosocial desire to help others is a basic human goal that matters to an individual's happiness. We employ both longitudinal and cross-sectional data to demonstrate that work-related prosocial motivation is associated with higher subjective well-being, both in terms of current happiness and life satisfaction later in life. Cross-sectional data also suggest that perceived social impact (the belief that one's job is making a difference) is even more important for happiness than the prosocial desire to help. The results show that the relationship between prosocial motivation and happiness is not limited to government employees, suggesting that in this aspect of altruistic behavior, public and private employees are not so different.